The Impact of Diversity in Information Society to Consumers - Rahmanita Ginting (Jurnal InterAct, 2015)
The aim of  this paper  is to analyze  the impact  of diversity in information  society as consumers. The society we currently live in is an information society, because our economy primarily depends on the production and consumption of information. Today the media are changing our  world in  many ways,  in the  rise of  the internet,  the integration of communication technologies, shifting media empires, new lifestyles, challenging career, changing regulations, shifting social issues and a new dynamic of power in society. The source of the dynamic of social change, the diversity impact and what are seen as epochal and global transformations in the structure of the economy, in social stratification, politics and culture is a technological paradigm based upon a cluster of innovation in information and technological paradigm. The transition to an information society is driven in part by rapid changes in technology such as computer and digital television. We should no longer think about the various media of communication as completely distinct entities. Why do the media exist? Do the media shape culture or does culture shape the media? Information technology and media are converging in the information society. Technological change is increasingly shaking up conventional media and now the ‘old’ mass media are responding with the innovation of their own. When new media enter our homes, media consumption patterns tend to change. In one survey of Pew Research Center, a quarter of Internet users said they watched television less since going online. Consumer’s differences improve or affect the use of information and communication technologies (ICT) among socially inclusive communities.